2014
DOI: 10.1371/journal.pone.0105158
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Mangrove Nursery Habitats Determines the Geographic Distribution of a Coral Reef Fish in a South-Pacific Archipelago

Abstract: Understanding the drivers of species' geographic distribution has fundamental implications for the management of biodiversity. For coral reef fishes, mangroves have long been recognized as important nursery habitats sustaining biodiversity in the Western Atlantic but there is still debate about their role in the Indo-Pacific. Here, we combined LA-ICP-MS otolith microchemistry, underwater visual censuses (UVC) and mangrove cartography to estimate the importance of mangroves for the Indo-Pacific coral reef fish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 57 publications
4
15
0
Order By: Relevance
“…The high prediction accuracies reached in our study were comparable to those obtained with similar methods for fish in mangrove areas (Paillon, Wantiez, Kulbicki, Labonne, & Vigliola, 2014). However, the attribution process frequently generates isolated unlikely predictions because sites are attributed independently of each other.…”
Section: Reconstruction Of Fish Movementssupporting
confidence: 83%
“…The high prediction accuracies reached in our study were comparable to those obtained with similar methods for fish in mangrove areas (Paillon, Wantiez, Kulbicki, Labonne, & Vigliola, 2014). However, the attribution process frequently generates isolated unlikely predictions because sites are attributed independently of each other.…”
Section: Reconstruction Of Fish Movementssupporting
confidence: 83%
“…Although we did not tag the observed fishes to determine their origin, we have previously shown, using stable isotope signatures in otoliths and muscle tissue of the yellowtail snapper Ocyurus chrysurus (a high-dependence species) and French grunt Haemulon flavolineatum (a low-dependence species), that even though adults can disperse over long distances, most (but not all) of the dispersal from nurseries onto reefs is concentrated at their nearest nursery habitat in Curaçao and Bonaire (Verweij et al 2008, Huijbers 2012, Huijbers et al 2013, and a similar mechanism has been confirmed for several Indo-Pacific species (e.g. Nakamura et al 2008, Kimirei et al 2013b, Paillon et al 2014. Hence, the best explanation for the spatially skewed distribution of nursery-dependent species is the enhancement of reef populations by nursery habitats in conjunction with high retention due to restricted dispersal from nurseries, with little effects of local habitat characteristics.…”
Section: Discussionmentioning
confidence: 78%
“…Adult population sizes can also be influenced by the size of nurseries and/or propagule densities (Halpern et al 2005, Grober-Dunsmore et al 2007, Jones et al 2010, Paillon et al 2014, Serafy et al 2015. Some studies have therefore examined the correlation of variables such as total nursery surface area to the size of offshore fish or shrimp populations (see reviews by Manson et al 2005, Nagelkerken et al 2008a, Blaber 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Indo‐Pacific: Kimirei, Nagelkerken, Mgaya, & Huijbers, ; Mellin, Kulbicki, & Ponton, ) and Lutjanidae (e.g. Tropical Atlantic: Aguilar‐Perera & Appeldoorn, ; Nagelkerken & van der Velde, ; Indo‐Pacific: Kimirei, Nagelkerken, Trommelen, et al, ; Nakamura et al, ; Paillon, Wantiez, Kulbicki, Labonne, & Vigliola, ), as well as some species from the Scarinae (e.g. Tropical Atlantic: Dorenbosch et al, ; Mumby et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Tropical Atlantic: Aguilar-Perera & Appeldoorn, 2007;Indo-Pacific: Kimirei, Nagelkerken, Trommelen, et al, 2013;Nakamura et al, 2008;Paillon, Wantiez, Kulbicki, Labonne, & Vigliola, 2014), as well as some species from the Scarinae (e.g. Tropical Atlantic: Dorenbosch et al, 2006;Mumby et al, 2004).…”
Section: Discussionmentioning
confidence: 99%